The First-to-File Principle and the Principle of Good Faith in Disputes Over Well-Known Trademarks for Non-Similar Goods (Case Study: Decision No. 2/Pdt.Sus-HKI/Merek/2023/PN Niaga MDN and Supreme Court Decision No.859K/Pdt.Sus-HKI/2024) - Mohammad Akmal Taris Hakim; Suherman Suherman (Warmadewa Press, 2026)
Legal protection for trademarks in Indonesia follows the “first to file” principle, which grants exclusive rights to the party that first registers the trademark. However, the application of this principle cannot be separated from the principle of good faith, which serves as a safeguard to ensure that trademark rights are not obtained through improper means, particularly in the protection of well-known trademarks. This study aims to analyze the legal framework regarding the